The Paleogene mammalian fauna of Santa Rosa, Amazonian Peru - Campbell, Kenneth E. 1943- (Science series (Los Angeles, Calif.), 2004)
This volume describes most of the known mammalian fauna of the Santa Rosa local fauna of eastern Peru, the first Paleogene vertebrate fauna to be reported from the forested, tropical lowlands of the Amazon Basin. ...The articles are heavily weighted toward taxonomic descriptions of species new to science, but there is also much discussion of the relationships of the new forms and what they might indicate about the evolution of the South American mammalian fauna.--Pref.